3X large magnifying glass with 10 anti-glare and fully dimmable LEDs [library of things] (MagniPros, 2021)
"Evenly lit viewing area. The best lighted magnifier for reading small fonts, low vision seniors, macular degeneration. The rectangular lens is especially design to simulate the way we naturally view things from left to right, the magnifying lens covers large viewing area without having your hands move all the time, lens is measured 4.35"x 2.7" and magnifies up to 300%. Made out of optical grade acrylic which is lighter and more scratch-resistant & shatterproof than glass while provides the same clarity level. Magnifies up to 3x(300%) without optical distortion. Optimal to enhance reading and viewing very fine details in books, newspapers, magazines, photographs, maps, electronics, miniatures, jewelry, pill bottles, medications, hobbies, models, and crafts of all kinds.This led magnifier is clinically proven to be ideal for anyone who strains their eyes to see words on a page because it magnifies and provides light without glare. The roller dimmer allows you to easily adjust the brightness level(peaks at 600 lumens) with the tap of a finger to achieve the perfect lighting for various tasks."-- Amazon description